Availability, prices and affordability of essential medicines for children: a cross-sectional survey in Jiangsu Province, China. Issue 10 (18th October 2018) - Sun, Xiaoluan; Wei, Jing; Yao, Yuan; Chen, Qiutong; You, Daiting; Xu, Xinglu; Dai, Jing; Yao, Yanping; Sheng, Jingyi; Li, Xin
Abstract : Objective: China has undertaken several initiatives to improve the accessibility of safe and effective medicines for children. The aim was to determine the availability, price and affordability of essential medicines for children. Design: Cross-sectional survey. Setting: Six cities of Jiangsu Province, China. Participants: 30 public hospitals and 30 retail pharmacies. Primary and secondary outcome measures: The WHO/Health Action International standardised methodology was used to collect the availability and price data for 40 essential medicines for children. Availability was measured as the percentage of drug outlets per sector where the individual medicine was found on the day of data collection, and prices were measured as median price ratios (MPRs). Affordability was measured as the number of days' wages required for the lowest paid unskilled government worker to purchase standard treatments for common conditions. Results: The mean availabilities of originator brands (OBs) and lowest priced generics (LPGs) were 7.5% and 34.2% in the public sector and 8.9% and 29.4% in the private sector. The median MPRs of LPGs in both sectors ranged from 1.41 to 2.12 and 1.10 to 2.24, respectively. However, the patient prices of OBs far exceeded the critical level in both sectors, with median MPRs ranging from 2.47 to 8.22. More than half of these LPGs were priced at 1.5 times their international reference prices in the public sector. Most LPGs were affordable for treatment of common conditions in both public and private sectors, as they each cost less than the daily wage for the lowest paid unskilled government worker. Conclusions: Access to essential medicines for children is hampered by low availability. Further measures to enhance access to paediatric essential medicines should be taken, such as developing a national essential medicine list for children and mobilising the enthusiasm of pharmaceutical firms to develop and manufacture paediatric medicines.